Studies Regarding The Bidirectional Relationship Between The Periodontal Disease And Hyperlipidaemia - Amelia Macovei-Surdu; Ioana Rudnic; Ioana Martu; Sorina Solomon; Liliana Pasarin; Silvia Martu (Romanian Journal of Oral Rehabilitation, 2013)
Introduction Hyperlipidaemia is influenced by the oral diseases, especially by the periodontal disease. The systemic exposure to infection challenges may have as a result the release of inflammatory cytokines, modifying the lipid metabolism, promoting hyperlipidaemia and atherosclerosis. Aim of the study The present study was conducted in order to assess the levels of cholesterol, low density lipoproteins (LDL), high density lipoproteins (HDL) and triglycerides on subjects with and without periodontal disease. Materials and methods We selected for the study a group of 36 male subjects and 24 female subjects, with the age between 30 and 50 years. We analysed separately the biochemical markers evolution, for a more efficient scientific presentation of the date obtained. Results and discussions The obtained values indicated a strong relation between the lowering of the lipid profile and the periodontal health; we also observed the diminishing of the plasmatic lipidc concentrations. The pathological levels of the triglycerides were around 6.5 times more frequent in periodontitis patients than in control group subjects, while no HDL difference was observed. Conclusions Pro-arteriogenic modifications of plasmatic lipids and blood glucose levels observed in periodontal disease patients may provide further evidence of a tight association between the periodontal disease and cardiovascular disease, with a possible role of hyperlipidaemia in periodontal disease.